Capturing Review of Protein and Vitamin D Needs in the Elderly - Bunga Janviera Firnanda; Naja Naura Noor Indrastata; Ashifa Yusrin Rahman; Durrotul Mahfudloh; Ismi Maulani; Dwi Rukma Santi (International Conference on Sustainable Health Promotion, 2025)
Background: Aging is a complex biological process, resulting in various physiological changes, psychosocial behavior, and cognitive changes. In addition, the elderly also experience changes in protein metabolism, and vitamin D. Where protein and vitamin D are very important for the elderly to stay healthy and the body’s metabolism continues to work normally. Objective: The aim of this study was to determine the protein and vitamin D requirements of the elderly population and evaluate the impact of these nutritional deficiencies on their physical and cognitive health. Methods: This research uses a literature review method using relevant quantitative or qualitative methods. Results: The results of the review of 22 journals showed that 9 out of 22 journals resulted in an influence between protein and elderly health problems, while 3 journals said there was no influence. Another 7 journals also showed an effect of vitamin D on the health problems of the elderly, while the other 3 journals showed no effect. Conclusion: Most studies show that there is an influence between protein and vitamin D requirements on physical and cognitive health problems in the elderly